Ofiurida ali kačjerepnica - Razpet, Marko (Obzornik za matematiko in fiziko, 2022)
We introduce the ophiuride, a lesser-known planar curve, first discussed by D. Uhlhorn at the beginning of the 19th century. An ophiuride is a set of points obtained by a simple geometric procedure, but it is also a pedal curve of a parabola, the inverse of a hyperbola, and the cissoid of a line and a circle. We will show that the ophiuride can be used to solve some cubic equations.
Keywords: Geometrija